2015
DOI: 10.1016/j.schres.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Quality of medical care for persons with serious mental illness: A comprehensive review

Abstract: Objectives Prior studies suggest variation in the quality of medical care for somatic conditions such as cardiovascular disease and diabetes provided to persons with SMI, but to date no comprehensive review of the literature has been conducted. The goals of this review were to summarize the prior research on quality of medical care for the United States population with SMI; identify potential sources of variation in quality of care; and identify priorities for future research. Methods Peer-reviewed studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 77 publications
0
84
0
Order By: Relevance
“…[61][62][63][64] In one VA study from 2001-2005, only 11 % of people with comorbid diabetes and SMI received medications to treat diabetes. 36 In a community sample, among people with schizophrenia who reported they had diabetes, 41 % reported not receiving antihyperglycemic treatment.…”
Section: Management Of Type 2 Diabetes and Other Cardiovascular Diseamentioning
confidence: 99%
“…[61][62][63][64] In one VA study from 2001-2005, only 11 % of people with comorbid diabetes and SMI received medications to treat diabetes. 36 In a community sample, among people with schizophrenia who reported they had diabetes, 41 % reported not receiving antihyperglycemic treatment.…”
Section: Management Of Type 2 Diabetes and Other Cardiovascular Diseamentioning
confidence: 99%
“…In a review, McGinty and colleagues found that the rate of ART receipt for persons with SMI in the U.S. (ranging from 51%–83% across studies) was below the recommended guidelines (85%) [38]. A similar trend has been noted in low and middle-income countries, where ART has traditionally been denied to persons with SMI.…”
Section: Secondary Hiv Preventionmentioning
confidence: 91%
“…Reasons for this disparity are multifaceted and include individual factors (e.g., health behaviors, medication induced weight gain, functional limitations) and social determinants (e.g., poverty, neighborhood, social supports) that contribute to poor health and reduced access to quality care, including HIV care. A recent review of the overall healthcare quality for individuals living with SMI in the U.S. revealed that antiretroviral therapy (ART) was less often prescribed for persons with SMI compared to the general population; however there was not a disparity for CD4 count and viral load monitoring [38]. Disparities in general and HIV-specific medical treatment for individuals living with SMI are global problems.…”
Section: Secondary Hiv Preventionmentioning
confidence: 99%
“…Once an established diagnosis of metabolic syndrome or T2DM is made, many of those with affective disorders are not offered timely treatment (McGinty et al, 2015). Thus, routine screening and prevention of metabolic abnormalities is only the first step.…”
Section: Physical Activity In the Management Of Cardio-metabolic Riskmentioning
confidence: 99%